Imágenes de Atenas en el mundo Ibérico: análisis iconográfico de la cerámica ática del siglo IV a. C. hallada en Andalucía Oriental - Sánchez Fernández, Carmen (Anuario del Departamento de Historia y Teoría del Arte, 1992)
Great quantity of pottery arrive to the Iberian Peninsula during the fourth century B.C. In Andalousia most of these pottery are Attic Red figured bell kraters. In the Greek world they were used to mix wine and water at the simposia. The iconographic study of the imported images -images of the banquet, of the amazons and dionysiacs- allow us to approach to the Iberian interpretation of these Greek pottery. In the indigenous contexts they have a funerary meaning.